Incremental Validity of Character Strengths as Predictors of Job Performance Beyond General Mental Ability and the Big Five - Harzer, Claudia; Bezuglova, Natalia; Weber, Marco (Frontiers in Psychology, 2021)
Over the last decades, various predictors have proven relevant for job performance (e.g., general mental ability [GMA], broad personality traits like the Big Five). However, prediction of job performance is far from perfect, and further potentially relevant predictors need to be investigated. Narrower personality traits like individuals’ character strengths have emerged as meaningfully related to different aspects of job performance. However, it is still unclear whether character strengths can explain additional variance in job performance over and above already known powerful predictors. Consequently, the present study aimed at (1) examining the incremental validity of character strengths as predictors of job performance beyond GMA and/or the Big Five traits and (2) identifying the most important predictors of job performance out of the 24 character strengths, general mental ability, and Big Five. Job performance was operationalized with multidimensional measures of both productive and counterproductive work behavior. A sample of 169 employees from different occupations completed web-based self-assessments on character strengths, GMA, and the Big Five. Additionally, the employees’ supervisors provided web-based ratings of their job performance. Results showed that character strengths incrementally predicted job performance beyond GMA, the Big Five, or GMA plus the Big Five; explained variance increased up to 54.8%, 43.1%, and 38.4%, respectively, depending on the dimension of job performance. Exploratory relative weight analyses revealed that for each of the dimensions of job performance, at least one character strength explained a numerically higher amount of variance than GMA and the Big Five, except for individual task proactivity, where GMA exhibited the numerically highest amount of explained variance. The present study shows that character strengths are relevant predictors of job performance in addition to GMA and other conceptualizations of personality (i.e., Big Five). This also highlights the role of socio-emotional skills like character strengths for the understanding of performance outcomes above and beyond cognitive ability.